Karakteristik Dielektrik Campuran Gas Karbondioksida (CO2) Dengan Nitrogen (N2) Dibawah Terpaan Medan Tinggi DC Polaritas Negatif - Prasetyo, Yansyah; Murdiya, Fri (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
Gas insulating material commonly used in electrical system is SF6 gas. SF6 gas is used as an insulator material in electrical system in transfer heat. However, SF6 gas is not environmentally friendly, and triggers the increase of global warming so it is necessary to conduct research to get other gas insulators as alternative materials such as gas Carbondioxide (CO2) and Nitrogen (N2). This study discusses the dielectric characteristics of a mixture of Carbondioxide (CO2) gas with Nitrogen (N2) under electrical stress (high voltage negative polarity). The study used spherical electrodes and needles with varying gap distances and we compared the gas breakdown voltage with ratio 25% CO2 : 75% N2, 50% CO2 : 50% N2, and 75% CO2 : 25% N2 respectively. The purpose this research is to find the maximum breakdown voltage for several ratio gases. From the test result obtained breakdown voltage in negative polarity is smaller than positive polarity. We also attempted the gases breakdown voltage 70 trials and it was indicated that the breakdown voltage varied -78,69 kV until -105 kV. The maximum discharge current recorded by an osciloscope was -104 A in 50% CO2 : 50% N2 ratio.Keywords : electrode, mixture insulation gas, polarity efect, dielectric power, negative polarity, breakdown voltage